Electromagnetic wave scattering from arbitrary 2D perfect conducting obstacles - Zhang, Hemei (2008)
In this project, the new method - the modified method of lines (MMoL) will be introduced. Also discuss the advantages and disadvantages of others numerical methods for solving the electromagnetic scattering problems, and introduce the applications of the finite element method using PDE (Partial Differential Equations) Toolbox in MATLAB.